2016
DOI: 10.1016/j.enbuild.2016.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a two-sided windcatcher integrated with wing wall (as a new design) and comparison with a conventional windcatcher

Abstract: In buildings, 60% of energy consumption is associated to HVAC systems. One solution to reduce this share is the application of natural ventilation systems. Windcatcher and wing wall are two well-known techniques for natural ventilation which have been used in different regions. Nevertheless, in areas with low wind speed such as tropical climate of Malaysia there is hesitation for application of natural ventilation systems. The integration of windcatcher with wing wall can potentially enhance the ventilation pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 46 publications
(64 reference statements)
1
30
0
Order By: Relevance
“…The review of current literature showed that significant research interest has been focused on a number of areas relating to the development of windcatcher technology [8][9][10][11][12][13][14][27][28][29][30] and its integration with cooling methods [23][24][25][26] such as heat pipes [15][16][17][18]. The research gaps that this study aims to address are the following; (1) There are limited studies on the experimental investigation of commercial windcatchers, particularly using field test method.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The review of current literature showed that significant research interest has been focused on a number of areas relating to the development of windcatcher technology [8][9][10][11][12][13][14][27][28][29][30] and its integration with cooling methods [23][24][25][26] such as heat pipes [15][16][17][18]. The research gaps that this study aims to address are the following; (1) There are limited studies on the experimental investigation of commercial windcatchers, particularly using field test method.…”
Section: Figurementioning
confidence: 99%
“…Several researchers [27][28][29][30] focused on the aerodynamics design and ventilation performance of wind towers and its components.…”
Section: Figurementioning
confidence: 99%
“…(3) Natural ventilation: To implement nZEB, an architectural design for inducing the reduction of the building energy demand through the effective influx of the outdoor air (i.e., natural ventilation) should be considered in the initial design stage. Generally, natural ventilation can be categorized based on two mechanisms: (i) buoyancy-driven ventilation by the vertical and horizontal temperature difference; and (ii) wind-driven ventilation by the pressure difference between the front and the back of the building (refer to Table 3) [29][30][31][32][33][34][35][36][37][38]. First, there are various previous studies related to buoyancy-driven ventilation [29][30][31][32][33][34].…”
Section: Part A-1: Passive Sustainable Designmentioning
confidence: 99%
“…As a result, the ventilation performance of the wind-catcher with a 30 • wing wall angle was superior to the other designs (45 • and 60 • ). Also, the ventilation performance of the new design was improved by 50% compared to the conventional wind catcher [37]. Mei et al (2017) analyzed the ventilation performance according to the building density level in an urban residential neighborhood using the CFD software program.…”
Section: Part A-1: Passive Sustainable Designmentioning
confidence: 99%
See 1 more Smart Citation